2023
DOI: 10.1088/1361-665x/aceb27
|View full text |Cite
|
Sign up to set email alerts
|

Shape recovery and mechanical properties investigation of carbon fiber dispersed bisphenol-A based epoxy composite

Abstract: Shape memory polymers (SMP) are employed in a wide range of fields because of their appealing properties, which include low density, low production costs, and ease of processing. In the present work, SMP composites were developed using ultrasonic mixing of carbon fiber (CF) and amorphous epoxy to enhance the properties of epoxy and shape memory effect. The prepared composites were tested for mechanical and shape memory properties. Flexural strength and tensile strength of pristine epoxy enhanced by 12.7% and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 68 publications
2
6
0
Order By: Relevance
“…The polymer samples had a 100% RR, indicating that they could return to the original length, and a 100% SF, indicating that they would not shrink once the load had been removed. These values are identical to those of shape-memory vitrimers synthesized from AESO [ 47 , 48 ] and similar to those of bisphenol A-based dual-cured polymers, which are above 95% [ 20 , 21 ]. Due to their thermo-responsive shape-memory properties, dual-cured polymers of vegetable oils are appropriate for a wide range of applications, such as electronics, biomedical devices, robotics, etc.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…The polymer samples had a 100% RR, indicating that they could return to the original length, and a 100% SF, indicating that they would not shrink once the load had been removed. These values are identical to those of shape-memory vitrimers synthesized from AESO [ 47 , 48 ] and similar to those of bisphenol A-based dual-cured polymers, which are above 95% [ 20 , 21 ]. Due to their thermo-responsive shape-memory properties, dual-cured polymers of vegetable oils are appropriate for a wide range of applications, such as electronics, biomedical devices, robotics, etc.…”
Section: Resultssupporting
confidence: 70%
“…Such dual-cured polymers have already been applied as dental materials, optical lenses, and SMPs [ 8 ]. Petroleum-based materials, such as those containing the bisphenol A fragment, are usually used for dual-curing reactions [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ] and shape-memory applications [ 20 , 21 , 22 ]. Bisphenol A, on the other hand, is believed to contribute to metabolic and endocrine disorders and water pollution [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Smallsized composite samples were fabricated for the shape memory testing, with dimensions measuring 50 mm × 10 mm × 0.5 mm, which are thinner than the samples employed in our previous study [26]. These thin strip composites were cast to carry out the shape memory experiments.…”
Section: Shape Memory Testing (U-bend Method)mentioning
confidence: 99%
“…It has been observed that shape memory actuators were made from SMPC comprising of carbon nanotubes [3], carbon black (CB) [23], thermosexpanded graphite [24], and magnetite [25], etc. The fillers, when dispersed in the SMP, enhances the mechanical properties such as modulus, strength, and recovery stress [26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation